Indigenous plants: a golden opportunity for discovery - Amber Farooqui (The Journal of Infection in Developing Countries, 2007)
Microbiologists and infectious disease experts are alarmed by the fact that effective antibiotics will not be available to treat severely ill patients in the near future because of the increasing emergence of antibiotic resistance. This threat is especially worrisome with regard to our lack of ability to combat multidrug resistant bacterial infections. This situation necessitates the development of new antimicrobial agents and their synergistic combinations. From conception of the idea to rational drug design, drug development is a decade-long process which requires the tireless efforts of scientists.